2018
DOI: 10.4103/jovr.jovr_36_16
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular lens calcification: Clinico-pathological report of two cases and literature review

Abstract: Purpose:We report the clinicopathological features and surgical outcomes of two cases of intraocular lens (IOL) calcification along with a review of the current literature.Case Report:The first patient was a 53-year-old woman with diabetes mellitus (type 2) who underwent phacoemulsification with posterior chamber IOL insertion (PCIOL), and pars plana vitrectomy. Significant clouding of the IOL was first noted after 1.5 years, and the IOL was replaced with an Artisan lens. The second patient was a 22-year-old w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…Various physicochemical studies have been applied to the analysis of hydrophilic IOLs' opacification. Among them, light and electron microscopy, as well as elemental or molecular surface analytic techniques, demonstrated that the opacification, similar to presented in this work, was related to calcium phosphate precipitation or adsorption of fatty acids and proteins on the IOLs' surface [22][23][24][25]. Sediments observed on IOLs are, in most described cases, distributed on the anterior and posterior surface of the optical zone, limited to the pupillary zone, but rarely appear in the peripheral part and haptics [26].…”
Section: Physicochemical Analysis Of Reported Casessupporting
confidence: 70%
See 3 more Smart Citations
“…Various physicochemical studies have been applied to the analysis of hydrophilic IOLs' opacification. Among them, light and electron microscopy, as well as elemental or molecular surface analytic techniques, demonstrated that the opacification, similar to presented in this work, was related to calcium phosphate precipitation or adsorption of fatty acids and proteins on the IOLs' surface [22][23][24][25]. Sediments observed on IOLs are, in most described cases, distributed on the anterior and posterior surface of the optical zone, limited to the pupillary zone, but rarely appear in the peripheral part and haptics [26].…”
Section: Physicochemical Analysis Of Reported Casessupporting
confidence: 70%
“…On the basis of the results of our research and reports known in the literature, we present a diagram (see Figure 9 ) of the probable mechanism of opacification of the C-Flex lens caused by deposits formed on its surface. As results from the analysis of cases described so far, the damage to the lens is caused by drying of its surface after the DSAEK procedure, particularly when the air injection is repeated [ 5 , 6 , 7 , 8 , 9 , 11 , 12 , 13 , 14 , 22 , 23 , 24 , 26 , 27 , 28 , 29 ]. The literature reports also indicate that the source of sediment growth can be related to the altered blood–aqueous barrier, which could allow protein penetration into the IOL surface.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 45 articles, five did not fulfil the inclusion criteria and were excluded from further analysis. The remaining included articles numbered 40 and were analysed using the Pierson tool …”
Section: Methodsmentioning
confidence: 99%